2014
DOI: 10.7314/apjcp.2014.15.1.413
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners' Perception of Tobacco Use and Cessation in Chhatisgarh, India - The Truth from Behind the Bars

Abstract: Background: Prisoners represent a population group that is disadvantaged, socially deprived and underprivileged, needing particular attention with regard to provision of necessary oral health care, health promotion and motivation and tobacco cessation. Considering the situation in prisons, smoking and tobacco chewing are burning issues related to health deterioration and economic loss that seem to be overlooked by the public health sectors. Aim: To assess prisoners' perception of tobacco use and cessation in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Similar to other studies 18,28 , almost all prisoners were aware of the harmful effects and malignant diseases associated with tobacco use. Additionally, our results are concomitant to those of Tiwari et al 30 where the majority of prisoners had previously attempted to quit, but failed to achieve this goal. Prisoners want to quit and change their lifestyle 28,31 , but they cannot do it without help.…”
Section: Number Of Cigarettes Per Daysupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to other studies 18,28 , almost all prisoners were aware of the harmful effects and malignant diseases associated with tobacco use. Additionally, our results are concomitant to those of Tiwari et al 30 where the majority of prisoners had previously attempted to quit, but failed to achieve this goal. Prisoners want to quit and change their lifestyle 28,31 , but they cannot do it without help.…”
Section: Number Of Cigarettes Per Daysupporting
confidence: 86%
“…Furthermore, some researchers believe that tobacco users must quit by themselves 30 . Efforts and interventions to help prisoners to cease tobacco use show more significant improvement among prisoners than from merely preventing them from using tobacco while incarcerated 33,39 .…”
Section: Number Of Cigarettes Per Daymentioning
confidence: 99%
“…The study revealed that tobacco consumption starts at the age of six and increases with the consumers' age. A study on KAP among school going children was done in neighboring state Chhattisgarh reported that 20.4% used tobacco (Tiwari et al, 2014a). Further to these evidences, in the current communication we report the prevalence of tobacco use and of leukoplakia and its association with tobacco use among the Gond tribe, a marginalized population living in the Kundam Block, Jabalpur district of Madhya Pradesh state in central India.…”
Section: Surendra Kumar* Malaisamy Muniyandisupporting
confidence: 54%
“…In addition to tobacco smoking, smokeless tobacco has also evidently shown its effect on various oral tissues (Al-Attas et al, 2014;Tiwari et al, 2014). With regard to the effect of shammah on oral mucosal tissues, limited studies have been published so far, which revealed the association Badr Abdullah Al-Tayar 1& , Mon Mon Tin-Oo 2 *, Modh Zulkarnian Sinor 2 , Mohammed Sultan Alakhali 3 between shammah and oral mucosal lesions such as oral leukoplakia-like lesions.…”
Section: Introductionmentioning
confidence: 99%